Development of an ultra-stretchable double-network hydrogel for flexible strain sensors - Li, Huijun (2021)
The applications of hydrogels are restricted by their weak mechanical properties due to the inefficient dissipation of energy in their intrinsic structures. A double-network (DN) hydrogel has been developed by combining an ionically crosslinked agar network, a covalently crosslinked acrylic acid (AAC) network, and a dynamic and reversible ionically crosslinked coordination between AAC chains and Fe3+ ions. A model has been proposed to reveal the mechanism of the improved mechanical properties in the DN agar/AAC–Fe3+ hydrogel. The hydrogen-bond crosslinked double helices of agar and ionic-coordination interactions of AAC–Fe3+ serve as sacrificial bonds during large deformation to dissipate the energy while the reversible AAC–Fe3+ interactions can be regenerated after stress relief, which greatly increases the toughness of the DN hydrogel. The prepared DN hydrogel demonstrates a remarkable stretchability with a break strain up to 3174.3%, a high strain sensitivity with a gauge factor of 0.83 under the strain of 1000%, and a good 3D printability which guarantee its various potential applications in flexible strain sensors for human motion detection, electronic skin, and soft robots.